Robot assisted sentinel lymph node biopsy using indocyanine green combined with carbon nanoparticles staining improved detection rates in breast cancer - Qinbo Wang; Qingyu Yang; Zuxiao Chen; Zongyan Li; Xiaoyan Fu; Yunxiang Luo; Yonghai Guo; Haiyan Li (Scientific Reports)
Abstract This study aimed to evaluate the safety and feasibility of robot-assisted sentinel lymph node biopsy using carbon nanoparticles with or without indocyanine green in breast cancer. A total of 52 patients with breast cancer who underwent robot-assisted sentinel lymph node (SLN) biopsy and subcutaneous mastectomy between August 2023 and September 2024 were extracted. Data collection included patient demographics, metastasis status, and surgery parameters. The primary endpoints encompassed dye usage, SLN identification rate, SLN metastasis rate, SLN biopsy sensitivity, and postoperative rehabilitation. We compared outcomes between indocyanine green (ICG) combined with carbon nanoparticles suspension injection (CNSI) staining versus CNSI staining alone in SLN biopsy. The mean age of participants was 51.4 ± 9.1years in the ICG + CNSI group versus 50.4 ± 10.6 years in the CNSI group; among them were 46 cases of infiltrating ductal carcinoma and six cases of ductal carcinoma in situ. The identification rate of SLN by dual-staining group was 100.0%, higher than that of CNSI group (91.6%) (p = 0.045 < 0.05). The median number of SLN counts was higher in the dual-staining group than in the CNSI group (5.75 for ICG + CNSI vs. 4.42 for CNSI; p = 0.355). 27 patients exhibited sentinel lymph node metastasis while 25 did not, the number of metastatic lymph nodes in dual staining group were higher CNSI group(4.5 for ICG + CNSI vs. 3 for CNSI; p = 0.453). Subgroup analysis revealed that the proportion of lymph nodes dual-stained with ICG and CNSI was significantly higher compared to those stained with CNSI or ICG alone (93.6% for ICG + CNSI vs. 72.1% for CNSI and 87.1% for ICG). Similarly, the proportion of positive sentinel lymph nodes (SLNs) dual-stained with ICG and CNSI was also greater than that achieved with either tracer individually (96.0% for ICG + CNSI vs. 84.0% for CNSI and 88.0% for ICG). Notably, CNSI staining was negative in two cases within the ICG + CNSI group, while one patient exhibited a false-negative staining pattern. Five instances of effusion and one case involving bleeding were reported; no significant differences emerged concerning postoperative complications, including breast drainage or hospital stay length, significant differences arose within numerical pain rating scale scores when comparing robot-assisted SLN biopsy positive versus negative groups (p = 0.021 < 0.05). Robot-assisted sentinel lymph node biopsy is an effective procedure for breast cancer, dual staining may facilitate improved detection rates pertaining to occult sentinel lymph node metastasis warranting further clinical exploration.